Faktor-Faktor yang Memengaruhi Keputusan Pembelian Konsumen pada Sanjai Mega di Kecamatan Akabiluru - Afriyona, Enjelita; Veronice, Veronice; Putra, Vicka Pramudya (Jurnal Bisnis Tani, 2025)
Sanjai Mega is one of the largest and most developed sanjai businesses in Akabiluru District. The existence of quite tight competition with similar businesses encourages business actors to pay more attention to efforts to attract consumer attention and strengthen competitiveness in order to achieve excellence in an increasingly competitive market, namely by understanding and considering the factors that influence consumers in deciding to purchase. The purpose of the study was to determine the effect of product quality, brand image, taste, service quality and culture on consumers in deciding to purchase at Sanjai Mega. The study was conducted in January-May 2025 in Akabiluru District, Lima Puluh Kota Regency, West Sumatra. The approach applied was quantitative by utilizing an instrument in the form of a questionnaire distributed to 100 respondents using a purposive sampling technique. Data sources were collected through two sources, namely primary data including observation, interviews, documentation and secondary data obtained based on relevant literature. Data analysis was carried out using SPSS by reviewing the effect of independent variables on the dependent variable. The study obtained results where simultaneously or partially product quality, brand image, taste, service quality and culture had significant value and had a positive effect on consumers in deciding to purchase.